(untitled) (Global Journal of Medical Research, 2023)
This survey aims to compare the level of knowledge attitudes and practices of the population towards coronavirus infection with the results of the baseline survey result to define the challenges faced by the participants and the behavioral changes when they have overcome and are adapting to the new style to develop and disseminate evidence-based recommendations for decision-makers who are dealing with the pandemic A total of 1896 people aged 15-60 years old participated in the study The survey data were collected using quantitative questionnaire and qualitative observation methods The survey questionnaire consisted of 45 questions of 6 chapters demographic knowledge attitude and adaptation practice towards coronavirus infection patient satisfaction with health care service delivery and information demand